ISLAMIC PHILANTHROPY AND SOCIAL ACTIVISM BASED ON MOSQUE OF Al-HIDAYAH IN SLEMAN YOGYAKARTA - ulil abshor; Muhammad Irham (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2022)
This study discussed how Mosque as the community of Muslim was able to finance social activities and conducted the program of community empowerment through the practice of Islamic philanthropy. By taking a case in a village in Sleman Regency, Yogyakarta, at where getting a Mosque that had been oriented toward religious and social activities of the community, namely the Mosque of Al-Hidayah Purwosari Sinduadi Village, Mlati District. This research aimed to see how the Mosque's involvement in philanthropic activities led at the program of local community empowerment. This research is important in doing because of the mosque's ability to collect and manage the fund of philanthropic for social activities. The data of this study were obtained through step ny step doing interview, observation, documentation and religious literature relevant to this study. The result of this study indicated that the fund of philanthropic came from zakat, infaq, alms and endowments that have been collected are distributed in the program of community empowerment which covered four main fields namely da'wah, education, social and economy. Finally, this study concluded that Mosque today was not only oriented toward worship, but also led to the programs of sustainable community empowerment through the practice of Islamic philanthropy.